Impeded phase transition in 1T-TaS2: Thermoelectric fingerprint of long-lived mixed states. (January 2020) - Ludwiczak, K.; Lacinska, E.; Binder, J.; Lutsyk, I.; Rogala, M.; Dabrowski, P.; Klusek, Z.; Stepniewski, R.; Wysmolek, A.
Abstract: 1T-TaS2 is a material that belongs to the family of transition metal dichalcogenides and features a rich phase diagram including different charge density wave states. So far, most techniques used to study this material focus on either very local properties on the atomic scale or use global measurements of the whole sample like the electrical resistance. Here, we report on the influence of micrometer scale laser illumination on the global electric properties of a bulk sample. Thermoelectric effects are found to be responsible for a large electric response to the laser illumination. This effect is used to develop a method that allows to spatially map the thermoelectric properties of a 1T-TaS2 sample on the millimeter scale with micrometer resolution. We show that a specific temperature sweep can impede the phase transition, allowing to study long-lived mixed states, consisting of two phases. With this method we are able to image metastable states occurring in the transition between the nearly commensurate and commensurate charge density wave state in bulk 1T-TaS2 and compare the results to Raman spectroscopy. Highlights: Spatially resolved photo-induced voltages yield thermoelectric maps of 1T-TaS2 . Long-lived mixed states of an impeded phase transition were successfully mapped. Raman spectroscopy confirms the coexistence of two phases within the laser spot.